(3SQGL GdXdeI hTeS GdMceIs - (3YHO GdcQje Hf YKeGf GdQjaj, GdeNJajs
(3ChdgG (B:s
(3bGd GagehG eYfi eGCbhd jG Phi GdYbhd QGi Gdedc QjGf ai ReGf jhSa Yde QDjG abGd dhRQGFg aSQhgG abGdhG CVZGK CMdGe s
(3BNQgG (B:s
(3hGYde jG CNj Ef CPgGf GdHTQ JbJUQ Yf eYQaI TF EdG eG LYd hGdMeO ddg Ydi eG CfYe Hg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3Jdjg aGFOIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B983s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs